Partisipasi Petani Terhadap Program Rehabilitasi Lahan Rehab Kawasan Meru Betiri di Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember - Charistandi Firmana; Lenny Widjayanthi (Jurnal KIRANA, 2020)
of the Republic of Indonesia and is located in Jember Regency. Meru Betiri National Park (TNMB) is a conservation area that functions as a life support system which also acts as a means of supporting research, knowledge and education as well as supporting agricultural cultivation, recreation, and tourism and is directly adjacent to the village of Wonoasri, which is the fostered village of the Park. Meru Betiri National. Wonoasri Village was appointed as TNMB's target village because of its location which is one of the supporting villages for the conservation area. This study to study (1) the reasons why farmers participated in the land rehabilitstion program for rehabilitation land in the meru betiri area in Wonoasri Village, Tempurejo District, Jember Regency, (2) the participation process that occurred in the land rehabilitation program for the Meru Betiri area in Wonoasri Village, Tempurejo District, Jember Regency. The determination of the research area was carried out deliberately (purposive method). The research used qualitative method. research area used was Wonoasri Village, Tempurejo District, Jember Regency. The method of determining information in research that uses done purposively is selected with certain considerations and goals. The results showed that: (1) rehab farmers participate in the rehabilitation program for rehab land to conserve forests again, (2) Rehab farmers are directly involved in the planning process to evaluate economic benefits. Keywords: Taman Nasional Meru Betiri, Wonoasri, Land Rehabilitation